2010
DOI: 10.1016/j.electacta.2010.01.063
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous-to-crystalline transition of silicon-incorporated anodic ZrO2 and improved dielectric properties

Abstract: Sputter-deposited zirconium and Zr-16 at.% Si alloy have been anodized to various voltages at several formation voltages in 0.1 mol dm −3 ammonium pentaborate electrolyte at 298 K for 900 s. The resultant anodic films have been characterized using X-ray diffraction, transmission electron microscopy, Rutherford backscattering spectroscopy, glow discharge optical emission spectroscopy, and electrochemical Capacitances of the anodic zirconium oxide are highly enhanced by incorporation of silicon due to reduced fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 49 publications
1
20
0
Order By: Relevance
“…In contrast, it has been realized that capacitances of crystalline anodic oxides on Zr-Ti alloys become higher than those on titanium and zirconium [11]. Recently, we have also found marked enhancement of the capacitance of crystalline anodic ZrO 2 by the incorporation of silicon species, although SiO 2 has low relative permittivity [12]. Thus, foreign species-incorporated anodic ZrO 2 is of interest as a dielectric.…”
Section: Introductionmentioning
confidence: 81%
“…In contrast, it has been realized that capacitances of crystalline anodic oxides on Zr-Ti alloys become higher than those on titanium and zirconium [11]. Recently, we have also found marked enhancement of the capacitance of crystalline anodic ZrO 2 by the incorporation of silicon species, although SiO 2 has low relative permittivity [12]. Thus, foreign species-incorporated anodic ZrO 2 is of interest as a dielectric.…”
Section: Introductionmentioning
confidence: 81%
“…16 A good correlation between the migration rates of cations and their single metal-oxygen bond energies has been reported. [17][18][19] The cation species with lower metal-oxygen bond energies migrate faster toward the film/electrolyte interface. The metal-oxygen bond energies decrease in the following order: Si 4+ 16 .…”
Section: Discussionmentioning
confidence: 99%
“…At the silicon content of 16 atom %, the average ox value is 21.7, being slightly smaller than that of pure zirconium. 25 Larger ox value of the anodic film formed at 100 V on the Zr-10 atom % Si film in comparison with that at 20 V may be associated with an amorphous-to-crystalline transition of the anodic film. The formation voltage dependence of ox becomes less significant for the anodic films on the Zr-16 at % Si film, probably because the relative thickness of the outer crystalline layer is reduced largely by the increase in silicon content to 16 atom %.…”
Section: Journal Of the Electrochemical Society 157 ͑12͒ C444-c451 ͑mentioning
confidence: 99%
“…The silicon-free outer layer is relatively thin, for both the Zr-10 and 16 atom % Si films, due to the low transport number of cations in amorphous anodic zirconia. 15,25 Since crystalline anodic oxide films are usually developed on zirconium metal, the outer silicon-free amorphous layer should be more readily crystallized during anodizing, compared with the inner silicon-containing layer. In addition, it has been reported that an amorphous-to-crystalline transition of anodic oxides during anodizing of niobium and Ti-Si alloys is initiated at the location that an air-formed oxide film is present before anodizing.…”
Section: Journal Of the Electrochemical Society 157 ͑12͒ C444-c451 ͑mentioning
confidence: 99%
See 1 more Smart Citation